Dysregulated Apoptosis and Autophagy in Childhood Epilepsy: Correlation to Clinical and Pharmacological Patterns - Ahmed, Ahmed El-Abd; Hassan, Mohammed H.; Abdelfatah, Asmaa A.; Bakri, Ali Helmi (Neuropediatrics, 2024)
Objectives We aimed to assess the serum levels of caspase-3 as a marker of apoptosis and microtubule-associated protein 1A/1B-light chain 3 (MAP1-LC3) as an autophagy marker in epileptic children with various clinical and pharmacological types.Methods This case–control study was carried out on 90 participants (50 pediatric patients with epilepsy and 40 healthy matched children), the patients were categorized into three groups: Group (A): 25 pharmacosensitive epilepsy, Group (B): 25 pharmacoresistant epilepsy, and Group (C): 40 (age, sex, and body mass index) matched healthy children selected as controls. Serum caspase-3 and MAP1-LC3 were measured in all study groups, using commercially available ELISA kits.Results Serum caspase-3 was significantly higher among epileptic children, especially in the pharmacoresistant group, cases managed with multiple antiepileptic drugs, and cases with abnormal EEG findings. Conversely, circulating MAP1-LC3 levels showed a significant reduction in epilepsy cases, particularly in pharmacoresistant cases, in cases treated with multiple antiepileptic drugs, and in cases with abnormal EEG data. A significant negative correlation between serum caspase-3 and MAP1-LC3 was found among epileptic children (r =  −0.369, p = 0.0083). Serum caspase-3 was a more valid biomarker in helping diagnose childhood epilepsy, while serum MAP1-LC3 was more valid in predicting pharmacoresistant type.Conclusion The study reveals that serum caspase-3 levels were significantly elevated, particularly in pharmacoresistant cases and those managed with multiple drugs. Conversely, MAP1-LC3 levels were significantly reduced in epilepsy cases, suggesting potential involvement of altered apoptosis and autophagy in childhood epilepsy.
Keywords: childhood epilepsy; apoptosis; autophagy; caspase-3; MAP1-LC3